Intersecting religion and culture: A comparative study of circumcision rites in the Old Testament and Yorùbá culture - Bamidele, Titilayo Lydia (Stellenbosch : Stellenbosch University, 2026)
Thesis (MPhil)--Stellenbosch University, 2026.